Method for Determining Pyrogenicity Using Monocytes: Prospects and Features of Application (Review) - E. O. Chechetova; N. P. Neugodova; O. V. Shapovalova (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. Determination of pyrogenic contaminants in medicines is a critical quality indicator that guarantees the preservation of life and health of patients. In order to control such substances, the biological indicator "Pyrogenicity" was introduced in the middle of the 20th century, which is based on the assessment of the reaction of rabbits to the introduction of the test sample. In accordance with the 3R concept, since 2009, in addition to testing on rabbits, the European Pharmacopoeia has included a monograph of an alternative in vitro method - the Monocyte Activation Test. This test was included in the domestic pharmacopoeia in 2018 (OFS.1.2.4.0016.18 "Monocyte Activation Test"). However, to date, the method has not received wide application among manufacturers either in Russia or abroad due to the peculiarities of the test, related to the need for a significant amount of human blood to obtain monocytes, with a limited choice of reagent kits, etc. The "Pyrogenicity" test is still in demand in the field of determining pyrogenic impurities of any nature (bacterial endotoxins and non-endotoxin pyrogens). For more complete harmonization with European requirements, implementation of the 3R concept related to humane treatment of animals, the introduction of the monocyte activation test is one of the priority tasks.AIM. Evaluation of the possibility of using the monocyte activation test as a primary test for the determination of non-endotoxin pyrogens.DISCUSSION. The article describes pharmacopoeial methods for determining pyrogenic substances, analyzes in detail the method for determining pyrogens using human blood cells – monocytes. Currently, the monocyte activation test is the only in vitro test that allows determining the presence of pyrogens of any nature (bacterial endotoxins and non-endotoxin pyrogens). The test is a worthy example of implementing the strategy of replacing animal tests, it allows determining impurities in cases where control using other methods causes difficulties or cannot be performed. The main disadvantage that complicates the implementation of the test in routine control is the limited availability of human blood as a source of monocytes. Possible sources of monocytes that can be used to determine pyrogenicity, including animal blood cells, are discussed. In accordance with the trend to replace the in vivo test – "Pyrogenicity" with an alternative in vitro method, the need to master the application of the method in relation to biological and immunobiological medicinal products is shown.CONCLUSIONS. Based on the results of the theoretical analysis of the possibility of using the in vitro method as the main method for determining, first of all, non-endotoxin pyrogens, it was established that the world community is seriously determined to refuse the use of animals. The monocyte activation test is included in most pharmacopoeias of the world, as well as in the domestic pharmacopoeia, and is recommended for implementation as the main control.